PERDAPA SEBAGAI MULTIMEDIA INTERAKTIF PADA TEMA PEREDARAN DARAHKU SEHAT PEMBELAJARAN 1 KELAS V - Dewi Nilasari (JS (JURNAL SEKOLAH), 2023)
Abstract: Perdapa As Interactive Multimedia On The Theme Of My Blood Circulation Healthy Learning 1 Class V.  This research is motivated by the experience of researchers in the learning process that occurs in classes where there are problems in the form of students' lack of interest in learning. In teacher innovation learning in making learning media it is still not interesting, and the delivery of material from teachers is lacking and learning interactions during a pandemic are limited in time and scope. The impact of this problem is that most students do not understand the content of learning material, especially on the material theme 4 healthy is important sub-theme 1 my blood circulation is healthy learning 1. The purpose of this study was to determine the development, feasibility and practicality of interactive media. This study used the Research and Development (R&D) method and the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation) with the subject being teachers and fifth grade students at SD NEGERI WATES. The instruments used in this study were expert validation sheets, product assessment questionnaires, and learning outcomes questions in the form of posttests with analytical techniques in the form of questionnaires, interviews, observation and documentation. The conclusions from the results of this study are PERDAPA Interactive Multimedia gets an average score of 89.5% from material expert lecturers and media experts, meaning that the media created is valid.PERDAPA Interactive Multimedia is stated to be practical and obtains an average score of 94.5%, meaning that the multimedia that is made is very practical to use. PERDAPA Interactive Multimedia is stated to be effective obtained from an average student score of 80 which can be declared effective. Keywords : Development, Interactive Multimedia, Thematic, Human Blood Circulation, Rhyme Abstrak: Perdapa Sebagai Multimedia Interaktif Pada Tema Peredaran Darahku Sehat Pembelajaran 1 Kelas V. Penelitian ini dilatarbelakangi oleh pengalaman peneliti dalam proses pembelajaran yang terjadi dalam kelas yang terdapat permasalahan berupa kurang tertarik peserta didik dalam pembelajaran. Dalam pembelajaran inovasi guru dalam membuat media pembelajaran masih kurang menarik, serta penyampaian materi dari guru kurang dan interaksi pembelajaran dimasa pandemi terbatas waktu dan ruang lingkup. Dampak dari masalah tersebut adalah sebagian besar siswa kurang memahami isi materi pembelajaran terutama pada materi tema 4 sehat itu penting subtema 1 peredaran darahku sehat pembelajaran Tujuan penelitian ini untuk mengetahui pengembangan, kelayakan, dan kepraktisan media interaktif. Penelitian ini menggunakan metode Research and Development (R&D) dan model pengembangan ADDIE (Analisys, Design, Development, Implementation, Evaluation) dengan subjek guru dan siswa kelas V SD NEGERI WATES. Instrumen yang digunakan dalam penelitian ini berupa lembar validasi ahli, angket penilaian produk, dan soal hasil belajar berupa posttest dengan teknik analisis berupa kuisioner, wawancara, observasi dan dokumentasi. Kesimpulan dari hasil penelitian ini Multimedia Interaktif PERDAPA mendapatkan nilai rata-rata 89,5% dari dosen ahli materi dan ahli media, artinya media yang dibuat sudah valid. Multimedia Interaktif PERDAPA dinyatakan praktis dan memperoleh nilai rata-rata 94,5 % artinya multimedia yang dibuat sangat praktis digunakan. Multimedia Interaktif PERDAPA dinyatakan efektif diperoleh dari rata-rata nilai siswa sebanyak 80 dapat dinyatakan efektif.Kata Kunci: Pengembangan, Multimedia Interaktif, Tematik, Peredaran Darah Manusia, Pantun